Analysis Of Ethical Challenges In Customer Data Management In Small-Scale E-Commerce Msmes - Eva Trisnawati; Muhammad Nur Abdi (International Journal of Business and Quality Research, 2026)
The development of digital technology and e-commerce has provided great opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach and improve operational efficiency. However, behind these conveniences, various ethical challenges arise, particularly in customer data management. The collection of personal data through online forms, digital cashier applications, and marketplace platforms requires MSME players to act responsibly in accordance with the principles of business ethics and information technology ethics. This study aims to analyze ethical challenges in customer data management in small-scale e-commerce MSMEs, focusing on data privacy, information security, and compliance with business ethics principles. The research method used is descriptive qualitative with a literature study approach to relevant scientific journals, regulations, and official documents. The results of the study show that most MSMEs still have limitations in their understanding of digital ethics and customer data protection systems. These limitations have the potential to cause data leaks and reduce consumer trust. Therefore, it is necessary to increase awareness of digital business ethics, provide technology literacy training, and implement data protection standards in order to protect customer rights and ensure the sustainability of MSME businesses.